Pengaruh Aromatherapy Lavender terhadap Penurunan Tingkat Nyeri pada Ibu Post Sectio Caesarea - Sri Rahayu; Nur Khakimah; Madnur Sholeh; R. Teguh Adi P; Wahyuningsih Wahyuningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Sectio caesarean surgery is a surgical procedure that can effectively prevent ma- ternal and newborn deaths when used for reasons of medical indications. Post operative sectio caesarean can pose several risks of complications, one of which is pain and surgical wound infection. Non pharmacological approach aromatherapy as a complementary therapy to reduce postpartum pain. This case study aims to analyze the influence aromatherapy lavender on reducing pain levels in post sectio caesarean mothers by using the case study method pre and post test. The case study was carried out in 25 May 2025 – 07 June 2025. This type of case study is descriptive with the number of subjects used, namely three post partum mothers in the RSUD Batang private sector with pain assessment using a questionnaire Numeric Rating Scale (NRS). The results of the case study showed a change in pain intensity from a scale of 6-7 to a scale of 4-5. This shows an influence aromatherapy lavender on reducing pain levels in postpartum mothers caesarean section Giving innovation aromatherapy can be used as an independent nursing in- tervention so that it can be applied to patients regularly.